The Roles of the Colon Cancer Associated Transcript 2 (CCAT2) Long Non-Coding RNA in Cancer: A Comprehensive Characterization of the Tumorigenic and Molecular Functions - Radu Pirlog (MDPI AG, 2021)
Colon cancer-associated transcript 2 (CCAT2) is an intensively studied lncRNA with important regulatory roles in cancer. As such, cumulative studies indicate that CCAT2 displays a high functional versatility due to its direct interaction with multiple RNA binding proteins, transcription factors, and other species of non-coding RNA, especially microRNA. The definitory mechanisms of CCAT2 are its role as a regulator of the TCF7L2 transcription factor, enhancer of MYC expression, and activator of the WNT/β-catenin pathway, as well as a role in promoting and maintaining chromosome instability through the BOP1–AURKB pathway. Additionally, we highlight how the encompassing rs6983267 SNP has been shown to confer CCAT2 with allele-specific functional and structural particularities, such as the allelic-specific reprogramming of glutamine metabolism. Additionally, we emphasize CCAT2’s role as a competitive endogenous RNA (ceRNA) for multiple tumor suppressor miRNAs, such as miR-4496, miR-493, miR-424, miR-216b, miR-23b, miR-34a, miR-145, miR-200b, and miR-143 and the pro-tumorigenic role of the altered regulatory axis. Additionally, due to its upregulation in tumor tissues, wide distribution across cancer types, and presence in serum samples, we outline CCAT2’s potential as a biomarker and disease indicator and its implications for the development of resistance against current cancer therapy regiments and metastasis.